Excessive Gadget Exposure and Children Speech Delay: The Case of Autism Spectrum Risk Factor - Rizky Anugrah Putra; Ashadi Ashadi; Muhammad Fahruddin Aziz (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Smartphones and gadgets are considered as one of the main factors in children's speech delays, especially those under three years. This delay is also accompanied by a child's social impairment like the symptoms of the autism spectrum. This article attempts to demonstrate the statistical correlation between smartphone usage and children's speech delay. Employing a mixed method design by combining statistical inference and qualitative descriptive methods with 70 respondents who were parents of children 1 - 5 years old in Indonesia, the researchers collected data using questionnaires and interviews and further thematically analyzed the responses. This article could show a negatively significant correlation between the duration of gadget use and speech habits, which means that the longer a child spends time playing with gadgets, the worse his/her early-stage language proficiency will be. Thus, it can be concluded that the excessive usage of gadgets has a detrimental impact on children's cognitive and verbal growth. In addition, the researcher found that children with autism spectrum attributes had a relationship with the duration of gadget usage. Further implications on parenting and language teaching are discussed to examine the novelty of the findings.